The Relationship Between Probiotic Intake and Glycemic Profiles Among Metformin-Treated Type 2 Diabetes Patients - Rahma Ayu Larasati; Silviah; Farabillah Afifah; Siti Hadzul Aniyah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
The ideal management of Type 2 Diabetes Mellitus should evolve from mere glucose-lowering strategies to a more comprehensive framework encompassing personalized medicine, technological integration, and systemic organ protection. A significant number of patients with Diabetes Mellitus (DM) continue to suffer from mortality and serious complications despite being on pharmacological therapy. Although trillions of dollars are spent annually on its management, diabetes remains a leading cause of mortality, claiming millions of lives each year across the globe. Probiotics have been proposed as an adjunctive therapy due to their role in modulating gut microbiota and glucose metabolism. This study aimed to analyze the effect of probiotic supplementation on Fasting Blood Sugar (FBS) levels in T2DM patients receiving metformin monotherapy. This experimental study involved 32 respondents, divided into probiotic intervention and placebo groups. FBS levels were measured pre- and post-intervention. Statistical analysis using the Paired T-Test showed a significant reduction in FBS levels (p=0.019). Conclusion: Probiotic supplementation significantly reduced FBS levels in T2DM patients on metformin monotherapy. However, this reduction was not clinically significant, as the final FBS levels did not differ significantly between the probiotic and placebo groups.